2022
DOI: 10.21037/jtd-22-451
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between the VivaSight double-lumen tube and standard double-lumen tube intubation in thoracic surgery patients

Abstract: Background: Thoracic surgery often demands separation of ventilation between the lungs. It is achieved with double-lumen tubes (DLTs), video double-lumen tubes (VDLTs) or bronchial blockers. We tested the hypothesis that intubation with the VivaSight double-lumen tube would be easier and faster than with a standard DLT.Methods: Seventy-one adult patients undergoing thoracic procedures that required general anaesthesia and one-lung ventilation (OLV) were enrolled in this randomized, prospective study. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…The difference in FOB usage reported by the authors is still higher than the limit of 6.6% proposed by Larsen et al ( 24 ), but the more experienced operator, the lesser the need for FOB verification and the lesser the economic superiority. Moreover, the rate of tube repositioning in the study by Palaczynski et al is higher in the VDLT group, pretty close to statistical significance ( 15 ).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…The difference in FOB usage reported by the authors is still higher than the limit of 6.6% proposed by Larsen et al ( 24 ), but the more experienced operator, the lesser the need for FOB verification and the lesser the economic superiority. Moreover, the rate of tube repositioning in the study by Palaczynski et al is higher in the VDLT group, pretty close to statistical significance ( 15 ).…”
mentioning
confidence: 68%
“…Nevertheless, the most remarkable difference to previous evidence is the percentage of FOB usage both for intubation and for repositioning of the DLT. Palaczynski et al report a much lower need than previous studies since it was not necessary in any case of the VDLT group and only in 20.5% of the conventional DLT group (15). This again raises the issue of the real need for systematic FOB to verify the location of the DLTs, and even to reposition them, provided that airway management is performed by experienced professionals (as seems to be the case).…”
Section: Editorialmentioning
confidence: 94%
See 1 more Smart Citation
“…Video laryngoscope-assisted DLT intubation has been proved to be superior over traditional direct laryngoscope in terms of the intubation time and glottic view in multiple studies [ 14 ]. Not only the assisting tools that have been developed but DLT itself could be equipped with a video system, and this consequently reduces the need for fiberoptic bronchoscopy [ 15 ], with which the intubation time could be shortened and the success rate could be improved for senior anesthesiologists in a manikin model [ 16 ]. Limited studies on video stylets in ET/DLT intubations have demonstrated their values in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [ 6 ] proved that the Trachway ® stylet could achieve faster left-sided DLT intubation (24 ± 4 s) compared with that of ML (48 ± 11 s) in a total sample size of 60. In a clinical study with a much larger sample size, Yang et al [ 5 ] found that compared with ML, the Optiscope ® RVS (Pacific Medical, Seoul, Republic of Korea) not only reduced DLT intubation time (15 s [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], but it also improved first-attempt success rates significantly in both left- and right-sided DLT intubation. Seo H and colleagues [ 17 ] even successfully used Clarus stylet-assisted DLT intubation for a patient with a possibly difficult airway.…”
Section: Discussionmentioning
confidence: 99%